2009
DOI: 10.1016/j.juro.2009.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Solifenacin Add-on Therapy to α-Blocker Treated Men With Residual Urgency and Frequency

Abstract: Solifenacin plus tamsulosin was well tolerated. There was a low incidence of urinary retention requiring catheterization. At week 12 solifenacin plus tamsulosin decreased daily micturitions and urgency episodes. Only urgency reached statistical significance vs placebo plus tamsulosin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 20 publications
3
88
0
2
Order By: Relevance
“…Some have reported that initiating combination therapy to all male LUTS/OAB patients showed significant improvements in their reported QoL compared with α-adrenergic antagonist monotherapy [5,14]. Others have adopted antimuscarinics add-on therapy to an ongoing α-adrenergic antagonist treatment in men with residual OAB symptoms [3,4,13]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some have reported that initiating combination therapy to all male LUTS/OAB patients showed significant improvements in their reported QoL compared with α-adrenergic antagonist monotherapy [5,14]. Others have adopted antimuscarinics add-on therapy to an ongoing α-adrenergic antagonist treatment in men with residual OAB symptoms [3,4,13]. …”
Section: Discussionmentioning
confidence: 99%
“…TIMES, ADAM, VICTOR, and many other similar studies that have evaluated the effect of antimuscarinics in men have incorporated questions about the patient's perception of treatment benefit as the primary endpoint [3,4,5]. This was so because of the assumption that the patient can provide a global response assessment that weighs the risks and benefits of treatment [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with symptoms of OAB, the addition of an antimuscarinic agent such as solifenacin, fesoterodine, tolterodine, or oxybutynin following initial treatment with an alpha1a-selective alpha-blocker has been shown to improve persistent storage symptoms to a greater degree than the alphablocker alone. [14][15][16][17][18] In men with predominant storage LUTS, antimuscarinic monotherapy is well tolerated and improves symptoms such as bedwetting and urgency urinary incontinence. [19][20][21][22] A concern with the use of antimuscarinics in men with BPH is the risk of acute urinary retention (AUR).…”
Section: Antimuscarinicsmentioning
confidence: 99%